Analisis Pengaruh Keputusan Resign dari Bank Konvensional terhadap Keharmonisan Rumah Tangga (Studi Kasus pada Komunitas Xbank di Kota Balikpapan) - Maghficilla Yeria Anugerah Gusti; Winning Son Ashari (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The decision to resign from a job is not easy for some people, especially since this job is a dream job and has promising job prospects such as being a bank employee, but of course this decision has been carefully thought out for people who want to leave that job. For someone who is married, the decision to resign certainly has an impact on their home life. The aim of this research is to examine the causes and influence of the resignation of the XBank community in Balikpapan City from conventional banks on household harmony. This type of research is field research. Researchers collected data by conducting interviews with members of the XBank community in Balikpapan City. The research results revealed that the reason the XBank Community in Balikpapan City decided to resign was the existence of usurious activities and transactions. Another reason was found to be changes in terms of time spent with family due to a break in focus regarding career or family. The influence of the decision to resign from a conventional bank has led to many changes, for example changes in lifestyle and not easily adapting to changes in income at work other than conventional banks where the income is stable and adequate.